Analysis Of Challenges And Implementation Of Digital Health Policy Transformation: A Literature Review - Novitayanti Pongsapan; Andriyana Abdullah; Abdul David Pongsapan (CV. AFDIFAL MAJU BERKAH, 2026)
The acceleration of global health digitalization offers significant potential to improve public care quality; however, its practical execution frequently encounters multidimensional barriers and threatens to widen the digital health divide. Objective: This study aims to comprehensively evaluate the policy typologies, service modalities, contemporary challenges, and real-world implications of international digital health implementations. Method: Utilizing a Systematic Literature Review (SLR) design aligned with PRISMA 2020 guidelines, literature searches were performed across PubMed, ScienceDirect, and Google Scholar databases for articles published between 2022 and 2026. Applying rigorous selection via the PICOS framework, 8 core articles were retrieved for extraction using thematic analysis. Results: The synthesis reveals that macro-level policies successfully diversified digital services into administrative (e-prescription), remote clinical care (Remote Patient Monitoring), and preventive governance (Digital Proximity Tracing). Instrumentally, e-health effectively reduces operational costs, enhances clinical quality, and bridges access gaps for marginalized groups, such as coastal and migrant populations. Nevertheless, the transition is severely hindered by fragmented data interoperability, insufficient digital literacy among professionals, ethical issues concerning AI algorithmic biases, and policy blindness toward technological determinism, which drives social exclusion. Conclusion: Integrating social determinants into digital health architecture is vital for establishing an equitable public health ecosystem. Policymakers must devise equity-centered regulations and system standardization, while medical institutions are urged to adopt structured literacy training to minimize internal resistance.